THE CONCEPT OF CATEGORY OF ADVICE LINGUISTICS - Xasanova Dilorom Shavkat qizi, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Abstract: A category in linguistics refers to a group of entities that have similar traits or abilities, and it is a crucial component in the structure of dialect. Syntactic, semantic, and morphological categories are important for arranging language data and promoting communication.